CHARACTERIZATION OF POTATO ACCESSIONS ACCORDING TO THEIR BIOLOGICAL AND ECONOMICALLY USEFUL TRAITS IN THE ENVIRONMENTS OF MURMANSK PROVINCE - T. E. Zhigadlo; S. N. Travina (Труды по прикладной ботанике, генетике и селекции)
Background. Studying new potato cultivars in extreme environments of the North as well as identification and development of source materials for breeding are vital challenges faced by for potato breeders. The article presents the results of a study that involved potato cultivars from the VIR global collection grown under the extreme climate conditions of Murmansk Province.Materials and methods. The study was conducted at the Polar Experiment Station of VIR in 2016‒2018, when 40 potato accessions, which had originated from 9 different countries and had been supplied by VIR, were analyzed. The research was based on the guidelines developed at VIR. The obtained data were compared with the standard reference (st) cv. ‘Khibinsky ranny’ (k-6928).Results. In the process of long-term research, cv. ‘Muromets’ (k-25268) was identified for early yield formation (128% vs st). Cvs. ‘Mestny’ (k-25286) from Ukraine and ‘Madeleine’ (k-25322) were outstanding for their earliness combined with productivity (115–140%). Cv. ‘Express’ (k-25262) was selected for its earliness (113%), productivity (128%), and high marketability (92%). Cvs. Aktyubinsky-2’ (k-25300), ‘Ushkonyr’ (k-25309), ‘Berkut’ (k-25250), ‘Gala’ (k-25270) and ‘Colleen’ (k-25224) demonstrated high productivity (106–131%). Cv. ‘Pamyati Kanaeva’ (k-25305) had the highest yield of 1154.0 g/bush (155%). The highest starch content of 14.4% was shown respectively by cvs. ‘Aytmurat’ (k-25448) and ‘Mestny No. 2’ from India. Twelve cultivars out of 40 appeared to be the most adaptable to the local growing conditions: ‘Muromets’, ‘Express’, ‘Pamyati Kanaeva’, ‘Volynskaya mestnaya’ (k25274), ‘Dovgenka’ (k-25275), ‘Sorokadenka’ (k-25293), ‘Gala’ (k-25270), ‘Reggi’ (k-25313), ‘Izmir’, form 2 (k-25272, Turkey), ‘Daphne’ (k-25296), and two local cultivars from Ukraine (k-25286 and k-25282).Conclusions. This study proved useful as it helped to analyze adaptive properties of potato cultivars and describe the studied material in the context of their basic biological and economic traits.